2010
DOI: 10.1007/s11255-010-9748-1
|View full text |Cite
|
Sign up to set email alerts
|

Octreotide reduces hepatic, renal and breast cystic volume in autosomal-dominant polycystic kidney disease

Abstract: A 43-year-old woman with autosomal-dominant polycystic kidney disease (ADPKD) received octreotide for 12 months, and this was associated with a 6.3% reduction in liver volume, an 8% reduction in total kidney volume and stabilization of renal function. There was also a reduction of cyst size in fibrocystic disease of breast. These data suggest that the cyst fluid accumulation in different organs from patients with ADPKD is a dynamic process which can be reversed by octreotide. This is the first report of a case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…For example, the mammalian target of rapamycin (mTOR) inhibitor rapamycin was thought to be a powerful drug for treating ADPKD, but it has not been effective (5,14,23). In recent reports, tolvaptan and octreotide have shown therapeutic effects in ADKPD, and both drugs target intracellular cAMP accumulation (4,7,12,16,18,24). In our study, ABCC3 was remarkably downregulated in polycystic kidney cells, and restoring ABCC3 decreased cell proliferation by reducing intracellular cAMP content.…”
Section: Discussionmentioning
confidence: 53%
“…For example, the mammalian target of rapamycin (mTOR) inhibitor rapamycin was thought to be a powerful drug for treating ADPKD, but it has not been effective (5,14,23). In recent reports, tolvaptan and octreotide have shown therapeutic effects in ADKPD, and both drugs target intracellular cAMP accumulation (4,7,12,16,18,24). In our study, ABCC3 was remarkably downregulated in polycystic kidney cells, and restoring ABCC3 decreased cell proliferation by reducing intracellular cAMP content.…”
Section: Discussionmentioning
confidence: 53%
“…2,5,16,17,24 To date, the lowering of cAMP in cystic cholangiocytes by agonists of somatostatin receptors is the only available pharmacologic treatment for patients with symptomatic liver disease. 2,5,7,8 The efficacy of two synthetic somatostatin analogues, octreotide and pasireotide, has been previously evaluated by us in preclinical trials, and our data demonstrate that pasireotide is more effective than octreotide in suppressing hepatorenal cystogenesis. 16,17 Furthermore, we recently examined the synergistic effects of pasireotide and hydroxychloroquine on disease progression in PCK rats.…”
Section: Discussionmentioning
confidence: 61%
“…Recent clinical trials have found SST agonists to be efficacious in ameliorating the growth of liver in ADPKD / PLD (polycystic liver disease) [60][61][62][63]. Data thus far has clearly found Octreotide to be safe and effective in treating polycystic liver disease.…”
Section: Human Trialsmentioning
confidence: 99%